PENGARUH PENGETAHUAN, PENDIDIKAN, DAN PERILAKU IBU TERHADAP TINGKAT KESEHATAN BALITA DI PUSKESMAS RANTAU PANJANG JAMBI [THE EFFECT OF MOTHER'S KNOWLEDGE, EDUCATION AND BEHAVIOR ON THE LEVEL OF TODDLER HEALTH T RANTAU PANJANG COMMUNITY HEALTH CENTER JAMBI] - Masnah, Masnah; Zulfikar, Taufik; Wirawan, Chevie (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
Maintaining toddlers’ health from an early age is very important for their growth and development. Achieving good health in toddlers requires support from mothers, who play a crucial role in children’s growth and development; therefore, the author is very interested in conducting this study. The purpose of this research is to determine the influence of mothers’ level of knowledge, education, and behavior on the health status of toddlers at the Rantau Panjang Community Health Center in Jambi. This is a quantitative study with a cross-sectional design. The study population comprised 322 mothers who had toddlers and visited the Rantau Panjang Community Health Center, Jambi, from January 2024 to August 2024. Sampling used the Slovin formula, yielding a sample of 80 respondents. This study employed univariate, bivariate, and multivariate analyses. The results showed that most mothers had a good level of knowledge, namely 60 (75%); the majority had higher education, 43 (53.8%); and most exhibited good behavior, 60 (75%). There was an effect of mothers’ level of knowledge on toddlers’ health status at the Rantau Panjang Community Health Center, Jambi, amounting to 44.8%. There was an effect of mothers’ education on toddlers’ health status amounting to 10.7%. There was an effect of mothers’ behavior on toddlers’ health status amounting to 65.7%. Simultaneously, there was an effect of mothers’ knowledge level, education, and behavior on toddlers’ health status at the Rantau Panjang Community Health Center, Jambi, amounting to 66.3%.